Game of thrones. The complete fifth season [videorecording (DVD)] - Benioff, David; Benioff, David; Dinklage, Peter; Coster-Waldau, Nikolaj, 1970-; Headey, Lena; Clarke, Emilia, 1986-; Martin, George R. R. (Home Box Office, Inc., 2016)
"This season begins with a power vacuum that protagonists across Westeros and Essos look to fill. At Castle Black, Jon Snow struggles to balance the demands of the Night's Watch with those of the newly-arrived Stannis Baratheon, who styles himself as the rightful king of Westeros. Meanwhile, Cersei scrambles to hold on to power in King's Landing amidst the Tyrells and the rise of a religious group led by the enigmatic High Sparrow, while Jamie embarks on a secret mission. Across the Narrow Sea, Arya seeks an old friend while a fugitive Tyrion finds a new cause. And as danger mounts in Meereen, Daenerys Targaryen finds that her tenuous hold on the city requires some hard sacrifices. This season features some of the most explosive scenes yet, as the promise that "winter is coming" becomes more ominous than ever before."--Container.